Human behaviour modelling: an investigation using traditional discrete event and combined discrete event and agent-based simulation - Abdul Majid, Mazlina (2011)
This thesis presents a comparison between two simulation methods, namely Discrete Event Simulation (DES) and Agent Based Simulation (ABS). In our literature review we identified a gap in comparing the applicability of these methods to modelling human centric service systems. Hence, we have focused our research on reactive and different level of detail of proactive of human behaviour in service systems. The aim of the thesis is to establish a comparison for modelling human reactive and different level of detail of proactive behaviour in service systems using DES and ABS. To achieve this we investigate both the similarities and differences between model results performance and the similarities and differences in model difficulty performance. The comparison of the simulation methods is achieved by using a case study approach. We have conducted three case studies, the choice of our case study systems taking into consideration the number of different key proactive behaviours that can be observed. In the first case study (fitting room services) we consider single proactive staff behaviour, in the second case study (international support services) we consider two proactive staff behaviours and, finally, the third case study (airline check-in services) considers three proactive staff behaviours. The proactive behaviours considered are: taking charge from experience, taking the initiative to fulfil a goal and supervising by learning. To conduct our case studies we have created two sets of simulation models. The first set consists of one DES model for each of the case studies. As service systems have an organisational structure we could not implement our agent-based simulation models purely as agent-based models. Instead, for the second set we have created combined DES/ABS models (one for each case study), where the DES part represents the system and the ABS part represents the active entities inside the system (i.e. the people).With these models we have carried out two sets of experiments: Set A is concerned with modelling results performance, while set B is related to model difficulty performance. We have then conducted statistical analysis on the results of these experiments. Evidence from the experiments reveals that DES and combined DES/ABS are found suitable to model the reactive and most levels of proactive behaviour modelled in this thesis. In addition, combined DES/ABS is found more suitable for modelling higher levels of proactive behaviour (complex behaviour). Another finding from the experiments is that it is only worth representing complex proactive behaviour if it occurs frequently in the real system (considering the relation between modelling effort and impact). The contribution made by this thesis to the body of knowledge is the comparison of DES and combined DES/ABS for modelling human reactive and different level of detail of human proactive behaviour in service systems. This comparison will assist modellers who are new to the field of service systems modelling to make an informed decision on the method they should use for their own modelling, based on the level of proactiveness inherent in the real system and on the levels of difficulties they should expect for each method.